REGULATION OF SUGAR TRANSPORT IN ISOLATED BACTERIAL MEMBRANE PREPARATIONS FROM Escherichia coli - Kaback, H. R. (1969)
The experiments presented in this paper demonstrate that glucose transport via the phosphoenolpyruvate-phosphotransferase system as studied in isolated E. coli membrane preparations is subject to regulation by sugar-P's. Glucose transport in these preparations is inhibited by glucose-6-P, glucose-1-P, and, to a lesser extent, by other P-esters. There appear to be two inhibitory sites, one specific for glucose-1-P and related sugar-1-P's and the other specific for glucose-6-P and related sugar-6-P's. The inhibition by these sugar-P's is noncompetitive, and the inhibitory sites are separate, subject to independent control, and apparently are accessible from outside the membrane. Furthermore, glucose-6-P is able to reverse partially inhibition of glucose transport by glucose-1-P and vice versa. Preliminary evidence is presented indicating that glucose-1-P may play a central role in the regulation of sugar transport in general, by virtue of its ability to inhibit selectively the transport of sugars other than glucose.